Mind4Health: decolonizing gatekeeper trainings using a culturally relevant text message intervention - Colbie Caughlan; Amanda Kakuska; Jane Manthei; Lisa Galvin; Aurora Martinez; Allyson Kelley; Stephanie Craig Rushing (Frontiers Media S.A., 2024)
BackgroundWhen a person dies by suicide, it takes a reverberating emotional, physical, and economic toll on families and communities. The widespread use of social media among youth and adolescents, disclosures of emotional distress, suicidal ideation, intent to self-harm, and other mental health crises posted on these platforms have increased. One solution to address the need for responsive suicide prevention and mental health services is to implement a culturally-tailored gatekeeper training. The Northwest Portland Area Indian Health Board (NPAIHB) developed Mind4Health, an online gatekeeper training (90 min) and text message intervention for caring adults of American Indian/Alaska Native (AI/AN) youth.MethodsThe Mind4Health intervention was a multi-phase, single-arm, pre-and post-test study of users enrolled in the intervention that is available via text message (SMS) or via a 90 min online, self-paced training. We produced four datasets in this study: Mobile Commons, pre-survey data, post-survey data, and Healthy Native Youth website's Google Analytics. The analysis included data cleaning, basic frequency counts, percentages, and descriptive statistics. Qualitative data were analyzed using thematic content analysis methods and hand-coding techniques with two independent coders.ResultsFrom 2022 to 2024, 280 people enrolled in the Mind4Health SMS training, and 250 completed the 8-week intervention. Many messages in the sequence were multi-part text messages and over 21,500 messages were sent out during the timeframe. Of the 280 subscribers, 52 participated in the pre-survey. Pre-survey data show that 94% of participants were female, and nearly one-fourth lived in Washington state, 92% of participants in the pre-survey were very to moderately comfortable talking with youth about mental health (n = 48). Most participants interact with youth in grades K-12. Post-survey data demonstrate changes in knowledge, beliefs, comfort talking about mental health, and self-efficacy among participants. Mind4Health improved participant's skills to have mental health conversations with youth and refer youth to resources in their community.